Major incidents. Issue 8 (August 2020) - Bayliss, Richard; Hurst, Tom
Abstract: A major incident is one that causes casualties on a scale beyond the usual capabilities of the emergency and healthcare services usual ability to manage. Major incident planning and rehearsal is vital to ensuring an appropriate response. Delivery of a major incident response requires command and co-ordination within and between emergency services, hospitals and specialist charitable organizations. Casualty management will require the set up of major incident infrastructure on scene to effectively extricate, triage, treat and transport casualties to appropriate facilities. There is a role for specialist doctors within the pre-hospital phase of managing a major incident, either within the ambulance command structure or operationally. Debrief and reviewing previous major incidents may identify individual, local and systemic factors that could be altered to improve the response to a future incident.